Variation in lung cancer risk by smoky coal subtype in Xuanwei, China - Lan, Qing (2008)
Lung cancer rates in Xuanwei County have been among the highest in China for both males and females, and have been causally associated with exposure to indoor smoky (bituminous) coal emissions that contain very high levels of polycyclic aromatic hydrocarbons. There are numerous coal mines across the County. Although lung cancer risk is strongly associated with use of smoky coal as a whole, variation in risk by smoky coal subtype has not been characterized as yet. We conducted a population-based case-control study of 498 lung cancer cases and 498 controls, individually matched to case subjects on age (±2 years) and sex, to examine risk by coal subtype. Odds ratios (ORs) and 95% confidence intervals (CIs) for coal subtype were calculated by conditional logistic regression, adjusting for potential confounders. Overall, smoky coal use was statistically significantly associated with lung cancer risk, as compared to use of smokeless coal or wood (OR=7.7, 95% CI=4.5 to 13.3). Furthermore, there was marked heterogeneity in risk estimates for specific subtypes of smoky coal (test for heterogeneity: p=5.17 × 10(−10)). Estimates were highest for coal from the Laibin (OR=24.8, 95% CI=12.4 to 49.6) and Longtan (OR=11.6, 95% CI = 5.0 to 27.2) coal types, and lower for coal from other types. These findings strongly suggest that in Xuanwei and elsewhere, the carcinogenic potential of coal combustion products can exhibit substantial local variation by specific coal source.